Direct credit controls as a monetary policy tool - COTULA, F.; PADOA-SCHIOPPA, T. (PSL Quarterly Review, 2014)
Generally speaking, the application of credit ceilings confronts the monetary authorities with a number of political and technical problems, such as the acceptability of distortions of and limits to market forces, the difficulty of administrative controls, and so on. Moreover, a systematic analysis of the economic implications of credit ceilings still has to be made, probably because of the novelty of these policy instruments. The present paper studies the effects and scope of the application of credit ceilings, whether they be considered a substitute for monetary base management or as an additional tool. The analysis is developed on the assumption that the banking system is made of a single large bank with many branches. JEL: E51, E52, G28